Nanocrystalline Toothpaste Formulation of Usnic Acid and Antibacterial Activity Test Against Streptococcus Mutans - Henni Rosaini; Rina Wahyuni; Sapra Nadia; Wahyu Margi Sidoretno; Yan Hendrika (Poltekkes Kemenkes Riau, 2023)
Usnic acid is a secondary metabolic compound derived from the genus usnea which has antibacterial activity. This study aims to determine the formulation of usnic acid nanocrystalline toothpaste and its antibacterial activity. The formula was prepared in four concentrations, namely F0 (1% usnic acid nanocrystals without preservatives), F1 (preservative only), F2 (2% usnic acid nanocrystals), F3 (3% usnic acid nanocrystals) and F4 (4% usnic acid nanocrystals). All formulas were tested for physicochemical characteristics (organoleptic, homogeneity, pH, foam formation) and tested for antibacterial activity against Streptococcus mutans. The results of the physicochemical characteristics test showed that all formulas met the physicochemical quality requirements of toothpaste. Antibacterial activity test with well method produced inhibition diameters of F0 (12.87 mm), F1 (6.26 mm), F2 (13.79 mm), F3 (14.16 mm), F4 (14.47 mm) and Positive Control 22.26 mm. Statistical results using the One Way ANOVA method at the 95% level of confidence, followed by Duncan's test showed that there was a significant difference in the diameter of inhibition between each formula.